ECO-INNOVATIVE PROJECTS FOR TERRITORIAL DEVELOPMENT: EXPERIENCE AND PRACTICE OF THE EU - MARCHENKO, Olha; NOVYTSKA Nadiіa (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines strategies and approaches employed within the European Union to promote sustainable development of territories. It analyzes eco-innovative projects aimed at conserving natural resources and reducing environmental impact, drawing from the experience of leading countries in implementing ecological innovations. The necessity of adopting the experience of European countries in implementing eco-innovative solutions and integrating them into the development system of regions in Ukraine is justified. Given the increasing attention to environmental issues, particularly in light of climate change and other global challenges, this article is more relevant than ever. Today, environmental problems are becoming increasingly urgent and are a priority for many countries and regions worldwide. Development of territories considering environmental aspects is crucial for sustainable development and preservation of vital resources. The strategies employed in the EU can provide valuable experience and practical examples for other countries facing similar environmental challenges. The article analyzes the Global Innovation Index used to assess the "green" direction of economic development in countries worldwide. The focus is on the innovative policies of the European Union, particularly in the development of green technologies and innovations. An analysis of the driving forces and barriers to the development and implementation of eco-innovative solutions in European countries, including Poland, is conducted. The feasibility of borrowing the experience of the European Union in the implementation of "green" technologies for sustainable development of territories in Ukraine is demonstrated. The relevance of this topic is significant as environmental problems become increasingly pressing, requiring joint efforts from individuals, governments, and international communities. The experience and practices of the EU can serve as an important source of information and improvement of strategies for the development of territories in Ukraine considering environmental aspects.